Gloeotrichia echinulata genomes from the United States are nontoxigenic and likely geosmin producers - Theo W. Dreher; Robin Sleith; Edward W. Davis; Ryan S. Mueller; Peter D. Countway (Harmful Algae, 2026)

Characterizing seasonal persistence of low levels of Pseudo-nitzschia australis in the Gulf of Maine with environmental DNA - Sydney M. Greenlee; Robin S. Sleith; Damian C. Brady; Peter D. Countway (Harmful Algae, 2026)

Testate amoebae (Arcellinida, Amoebozoa) community diversity in New England bogs and fens assessed through lineage-specific amplicon sequencing - Olivia K. Dufour; Evie Hoffman; Robin S. Sleith; Laura A. Katz; Agnes K.M. Weiner; Taylor R. Sehein (European Journal of Protistology, 2024)

Global high-throughput genotyping of organellar genomes reveals insights into the origin and spread of invasive starry stonewort (Nitellopsis obtusa) - Robin S. Sleith; Kenneth G. Karol (Biological Invasions, 2021)
Aquatic invasive species are damaging to native ecosystems. Preventing their spread and achieving comprehensive control measures requires an understanding of the genetic structure of an invasive population. Organellar genomes (plastid and mitochondrial) are useful for population level analyses of invasive plant distributions. In this study we generate complete organellar reference genomes using PacBio sequencing, then use these reference sequences for SNP calling of high-throughput, multiplexed, Illumina based organellar sequencing of fresh and historical samples from across the native and invasive range of Nitellopsis obtusa (Desv. in Loisel.) J.Groves, an invasive macroalgae. The data generated by the analytical pipeline we develop indicate introduction to North America from Western Europe. A single nucleotide transversion in the plastid genome separates a group of five samples from Michigan and Wisconsin that either resulted from introductions of two closely related genotypes or a mutation that has arisen in the invasive range. This transversion will serve as a useful tool to understand how Nitellopsis obtusa moves across the landscape. The methods and analyses described here are broadly applicable to invasive and native plant and algae species, and allow efficient genotyping of variable quality samples, including 100-year-old herbarium specimens, to determine population structure and geographic distributions.

Ubiquity or not ubiquity: That is the question - Robin S. Sleith; Laura A. Katz (Molecular Ecology, 2019)
The nature of population structure in eukaryotic microbes has been the subject of intense debate, but until recently the tools to test these hypotheses were either problematic (e.g., allozymes that cannot detect all genetic changes) or beyond financial and technological limits of most laboratories (e.g., high throughput sequencing). In a recent issue of Molecular Ecology , Craig et al. (2019) use a genomic approach to investigate the population structure of a model alga, the chlorophyte Chlamydomonas reinhardtii (Figure 1). Using high throughput sequencing, read mapping, and variant calling, they detected strong signals of differentiation at a continental scale, while local patterns of admixture were complex. Population genomic techniques such as these have not been used extensively in studies of microbial eukaryotes and the fields of conservation genetics and evolution stand to benefit vastly from the adoption of these techniques to studies of diverse protist lineages.

New records of the rare North American endemic Chara brittonii (Characeae), with comments on its distribution - Kenneth G. Karol; Mitchell S. Alix; Robin W. Scribailo; Paul M. Skawinski; Robin S. Sleith; Joseph A. Sardina; John D. Hall (Brittonia, 2018)

Distribution of Nitellopsis obtusa (Characeae) in New York, U.S.A. - Robin S. Sleith; Amy J. Havens; Robert A. Stewart; Kenneth G. Karol (Brittonia, 2015)